Prosthodontic management of hypohidrotic ectodermal dysplasia: a case report - Emilija Bajraktarova Valjakova; Misevska, C.; Korunoska Stevkovska, V.; Gigovski, N.; Sotirovska Ivkovska, A.; Bajraktarova, B.; Guguvcevski, Lj (Dentitio, 2015)
Introduction: Ectodermal dysplasia (ED) is a hereditary disorder associated with developmental disorders of two or more structures of ectodermal embryonic origin. Hypodontia or anodontia of the primary and permanent dentition, poorly developed alveolar ridges and improper maxillo - mandibular relations, are the most common oral manifestations. Management of patients with ectodermal dysplasia requires a multidisciplinary team approach. Case presentation: A 6.5 year-old boy with hypohidrotic ectodermal dysplasia (HED) presented in this article, had typical features of HED: hypohidrosis, hypotrichosis, severe hypodontia, atrophic alveolar ridges, old-looking facial expression. According to the patient's age and clinical findings, removable complete over-denture prosthesis in both arches was the treatment of choice. Conclusion: In patients with ED, it is important to establish correct maxillo - mandibular relations and normal function of the dento-facial system (chewing, swallowing, and speaking). Prosthodontic treatment has a major impact on aesthetics and functions,facilitates psychological development and improves emotional condition and social life of the patient.